Histologic and histochemical studies on the palpebra tertia of holstein and brown swiss cows - Murat Boydak (Eurasian Journal of Veterinary Sciences)
The aim of study was lo determine histological structure of both nictitating membrane, itself and, its glands, to evaluate possible contribution lo the local immunity of the eye itself and the basic histological knowledge to be used as reference out on local interventions. For Ihese purposes a comparative histochemical and light microscopic evaluation of PT was carried out on the both sexes in Brown Swiss and Holstein cows. The periodic acid-Schiff (PAS).alcian blue pH=2.5 (AB) and PAS/AB at pH=2.5 combined staining was used to histochemical properties in Ihe glands of the PT.lt was observed thai Ihe PT of cows investigated had an "T" shaped hyaline cartilage, so-called cartilago palpebra tertia (KPT) which was covered with the continuation of conjunctival epithelial tissue in the medial canthus in cows.The epithelia of the both palpebral and bulbar faces, and free marginal aspect of the PT were stratified squamous epithelium as in conjunctiva.GII. palpebra tertia superficialis (GPTS) was observed as lobes surrounded by connective tissue capsule located around the KPT.AIthough the gll. palpebra tertia profundus (GPTP) were observed in the cow, it was lack of the histological and histochemical properties of the Harderian gland. The cows investigated wide lymphocytic infiltration areas were observed m the connective tissue. Especially, cows the areas formed lymphoid follicles in the fornix conjunctiva and lamina propria of the palpebral and bulbar aspects ol the PT.Branched tubuloalveolar construction of GPTS with mix secretion was found in cows. Varying degrees of pigmentation was observed over the free margin, palpebra I and bulbar aspects ol the PT in cows Elastic.reticular and collagen fibers were observed under Ihe epithelium and deeper parts of the lamina propria,Plasma cells were lound in groups in the connective (issue of the free margin,palpebral and bulbar aspects.and intralobular and interlobular interstitium of the GPTS and GPTP, Myoepithelial cells were found to be located in the corpus glandulae and walls ol the ducts systems of both GPTS and GPTP.